2009
DOI: 10.1080/19397030802576288
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and optimisation of a product recovery network

Abstract: An appropriate logistics network is an important element of the infrastructure of any product recovery company. Small and medium enterprises (SMEs) constitute a major fraction of the product recovery industry with a different business objective and scale of operation from those of original equipment manufacturers. This paper addresses the network design issues for SMEs involved in product recovery activities. A mathematical formulation is presented in an SME context and a subsequent simulation model is develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…While the emphasis in research and implementation of DES studies in the past has mostly been focused on such large organisations, there are some reported cases where DES has been applied to SMEs (Ahmed and Latif, 2010;Byrne and Heavey, 2004;Geraghty and Heavey, 1999;Hvolby et al, 2012;Jain and Leong, 2005;Jarkko et al, 2013;Liotta, 2012;Mahfouz et al, 2011;Mosca et al, 2005;Nisula and Pekkola, 2012;O'Kane, 2003;Swarnkar and Harding, 2009). Studies of SME simulation have been sporadic and mostly explored on a one off, case-by-case basis (Hvolby et al, 2012;Jarkko et al, 2013;Mahfouz et al, 2011) which is in line with reported expectation, as investigating simulation within the SME context presents a number of additional challenges (Liotta, 2012;O'Kane, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While the emphasis in research and implementation of DES studies in the past has mostly been focused on such large organisations, there are some reported cases where DES has been applied to SMEs (Ahmed and Latif, 2010;Byrne and Heavey, 2004;Geraghty and Heavey, 1999;Hvolby et al, 2012;Jain and Leong, 2005;Jarkko et al, 2013;Liotta, 2012;Mahfouz et al, 2011;Mosca et al, 2005;Nisula and Pekkola, 2012;O'Kane, 2003;Swarnkar and Harding, 2009). Studies of SME simulation have been sporadic and mostly explored on a one off, case-by-case basis (Hvolby et al, 2012;Jarkko et al, 2013;Mahfouz et al, 2011) which is in line with reported expectation, as investigating simulation within the SME context presents a number of additional challenges (Liotta, 2012;O'Kane, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…model that solved the location problem of disassembly, collection and distribution facility, aside providing optimal values of production and transportation quantities of manufactured and remanufactured products, have been proposed by Swarnkar and Harding (2009), and Demirel and Gökçen (2008), respectively. Regarding the development of efficient IMS for RL system, research studies covering Radio Frequency Identification technology as state-of-the-art IT solution approach appeared frequently in literature.…”
mentioning
confidence: 99%